The renaissance of confucianism in contemporary China - Fan, Ruiping (Springer Netherlands, 2011)
The Renaissance of Confucianism in Contemporary China features an important school of Confucianism in Mainland China today, 'Political Confucianism' powerfully articulated by Jiang Qing, author of the leading article in this volume. 'Political Confucianism' is unique: on the political side, it rejects many core values of liberalism, the dominant political ideology in the West; and on the 'Confucianism' side, it rejects the one-sided emphasis on the inner sageliness of ?New Confucianism? developed in Hong Kong and Taiwan in the last century. In this volume, the programmatic essay by Jiang Qing is followed by penetrating essays, either further expanding on or critically examining various themes of Jiang's original essay, by eminent scholars, many of whom are committed Confucians themselves. The volume concludes with an informative biography of Jiang Qing. It is a must-read for anyone who is interested in learning about the situation of Confucianism in contemporary China in particular and about Confucianism or contemporary China in general.